Planning and management modeling for treated wastewater usage - Ahmadi, L., author; Merkley, G. P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2008)
Due to urban growth, some agricultural lands have been replaced by residential, municipal, and industrial areas. In some cases the remaining agricultural land will not have enough water because of transfers from agriculture to M&I users. Therefore, in many places, especially in arid and semi arid regions, the use of treated wastewater as a reliable source of irrigation water has already been or will be considered in the future. Due to its unique characteristics, this new resource has many challenges that cannot be ignored, such as health issues, water quality, long- and short-term effects on soils and crops. This study considered the development of a new GIS-based model for planning and managing the reuse of treated wastewater for the irrigation of agricultural and green lands, considering various factors such as population and urban growth. The model is composed of several different modules, including an urban growth model. These modules help the user make better decisions for allocations of water resources to agricultural areas, considering factors such as crop types, crop pattern, water salinity, soil characteristics, pumping and conveyance costs and also by comparing different scenarios. Appropriate crops that can be grown with a specific water salinity and soil characteristics, proper water resources for each farm (according to pumping and conveyance costs, and analysis of water demand, and water supply) can be determined through the application of this model. The model can also rank agricultural areas and open spaces in and near an urban area according to their suitability for irrigated agriculture.
Urbanization of irrigated land and water transfers
Not digitized by CSUL Digital Services.
Presented at Urbanization of irrigated land and water transfers: a USCID water management conference on May 28-31, 2008 in Scottsdale, Arizona.